Variasi Genetik Pinus merkusii Menggunakan Penanda Mikrosatelit Kloroplas - ILG Nurtjahjaningsih; AYPBC Widyatmoko; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2011)
Using two chloroplast universal primers, haplotipic within and among populations of Pinus merkusii had been evaluated, in order to access paternal variation of this species. The aim of this study was to investigate variation of chloroplast microsatellite in P. merkusii. Using two universal chloroplast microsatelites, a total of 18 chloroplast haplotypes were found among 730 individuals surveyed in 10populations in Java. Private haplotypes mostly found at eastern Java populations. The number ofdetected haplotypes (Na) within populations ranged between 5 and 14. Variation of haplotypes (h) was relatively hight; it ranged between 0.727 and 0.858. Nei’s genetic distance among populations was very low (Da=0.030). Moreover, analysis of molecular variance (AMOVA) showed genetic variation originated from within population but the value was insignificant.It was concluded that private haplotypes found in eastern Java might show gene pool of P. merkusii in Java. These detected haplotypes are of important information for genetic resources conservation anf breeding strategy of P. merkusii.